Resveratrol protects against homocysteine‐induced cell damage via cell stress response in neuroblastoma cells. Issue 1 (18th July 2014) - Currò, Monica; Trovato‐Salinaro, Angela; Gugliandolo, Agnese; Koverech, Guido; Lodato, Francesca; Caccamo, Daniela; Calabrese, Vittorio; Ientile, Riccardo
<x xml:space="preserve">Abstract</x> Recent findings underscore that some natural compounds are responsible for specific biochemical effects, i.e., the activation of redox‐sensitive intracellular pathways and modulation of different stress proteins, such as heat shock proteins and sirtuins. Resveratrol, a natural polyphenol widely present in plants, has been shown to display various beneficial effects, including neuroprotection, in several pathological conditions. In the present study, by using differentiated SH‐SY5Y neuroblastoma cells, we investigated the potential protective effects of resveratrol against homocysteine‐induced neurotoxicity. We observed that homocysteine (100 µM) decreased cell viability while at the same time significantly increasing intracellular reactive oxygen species and DNA fragmentation. Cell pretreatment with resveratrol concentrations ranging from 1 to 5 µM elicited protective effects through the reduction of oxidative stress and genotoxic damage. In addition, we observed that resveratrol produced significant changes in the expression of both Hsp70 and sirtuin 1 (SIRT1). After homocysteine treatment in the presence of resveratrol, SIRT1 protein was found abundantly not only in the cytosol but also in the nucleus, as demonstrated by confocal laser scanning microscopy. The results of this study suggest that resveratrol is a potential protective agent against homocysteine‐induced neurotoxicity and that beneficial effects are accompanied by changes in cell stress response. Taken together, these features contribute to our knowledge of underlying mechanisms involved in resveratrol‐induced cell survival. © 2014 Wiley Periodicals, Inc.